The Bologna process: what should and should not be done? - Pacheco-Torgal, F. (2007)
The Bologna process aims to the construction of a European higher education area, with a system of easily readable and comparable degrees, promoting teachers and student’s mobility in order to foster European citizen’s employability and the international competitiveness of the European higher education system. It therefore presents an amazing opportunity to reshape academia curricula, particular in the case of engineering curriculum. In a knowledge-based economy, changing in a dramatic pace, new skills are needed. Skills like creative thinking, ecology insights, entrepreneurship, foreign languages learning, or even literature matter more than traditional core engineering issues. Unfortunately, some signs indicate that the Bologna process led only to a change in the length of the graduation cycles, which may become a lost opportunity to change our future into a sustainable and better one.